AN EVALUATION OF PUBLIC AQUARIUMS IN SÃO PAULO (BRAZIL) IN LIGHT OF THE “GLOBAL AQUARIUM STRATEGY FOR CONSERVATION AND SUSTAINABILITY - Holanda, Priscila Carvalho; Neto, Manuel Antônio de Andrade Furtado; Cabral, Nájila Rejanne Alencar Julião (Arquivos de Ciências do Mar, 2015)
The purpose of this study was to determine to what extent a sample of seven Brazilian public aquariums adhered to the guidelines of the World Association of Zoos and Aquariums – WAZA, in their in situ and ex situ efforts at environmental education, research and biodiversity conservation. Information was collected with a questionnaire containing 34 items covering the 9 pillars of the WAZA. Although all aquariums provided some form of environmental conservation, many were unfamiliar with important WAZA, EAZA and IUCN documents. Brazilian public aquariums are advised to join the WAZA community, assume greater responsibilities for conserving local ecosystems, create action plans and in-house animal ethics and welfare codes, intensify breeding programs, raise funds for biodiversity conservation and develop research policies. The study suggests how researchers, activists and aquarium managers can contribute to making the planet an ecologically healthier and safer place for present and future generations, and provides subsidies for further projects reflecting the role of public aquariums in the context of the current environmental crisis of the Anthropocene.